Kidney Injury in Children Infected with HIV, Followed at the Teaching Hospital of Borgou (Benin): Epidemiological and Clinical Aspects (Journal of Renal and Hepatic Disorders, 2021)
The history of kidney disease associated with HIV infection dates back to the years of HIV breakthrough. The objective was to study kidney damage in children infected with HIV at the Teaching Hospital of Borgou (Benin) in 2019. This was a cross-sectional, descriptive, analytical, matching-type study carried out from June 1, 2019 to September 30, 2019 at the pediatrics department of Teaching Hospital of Borgou (Benin). The study included HIV-positive children, followed in consultations, and whose parents gave their consent. The biological markers were demonstrated with urine dipstick. Glomerular filtration rate was calculated using the Schwartz test and classified according to stages. The dependent variable was the presence of at least one impairment (biological or functional). Sample size was determined by Schwartz’s method on the basis of one case for two controls. Sociodemographic, clinical, biological, and therapeutic data were collected. Comparisons were made using the Chi- square test or Fisher’s exact test. The identification of associated factors was possible using a multiple logistic regression model at 5% threshold. In total, we included 117 children, including 39 HIV-positive children. The average age was 8 ± 4.81 years and the gender ratio was 1:17. The frequency of kidney damage was 76.5%. Permanent proteinuria and at least two crosses on urine dipstick were present in 20.5%, leukocyturia in 2.6%, and proximal tubular dysfunction in 5.1%. Glomerular hyperfiltration was found in 38.5%, acute kidney injury in 38.5%, and chronic kidney injury in 5.1%. Associated factors were age (P = 0.004), presence of opportunistic infections (P = 0.00), and treatment adherence (P = 0.004). Kidney damage is common in HIV-positive children. Careful follow-up is necessary to avoid complications.
Keywords: Benin; HIV-positive; kidney disease; pediatrics